2019
DOI: 10.12957/jse.2019.40992
|View full text |Cite
|
Sign up to set email alerts
|

Background Concentrations of Chemical Elements in Sepetiba Bay (Se Brazil)

Abstract: This study intends to evaluate baseline concentrations of chemical elements for unpolluted sediments of Sepetiba Bay (SE Brazil). It analyzes the concentrations of potentially toxic elements (PTE) and other chemical elements (by Inductively Coupled Plasma Mass Spectrometry and Inductively Coupled Plasma Emission Spectrometry) from the upper part of the SP2 drillcore (or 2-SPT-1-RJ; with 50.30 m length), collected on the margins of Sepetiba Bay (at latitude 22° 55'S and longitude 43° 46'W). This core was descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
0
9
1
2
Order By: Relevance
“…On the other hand, similarly to the previous region, the northern area presents the highest levels of Cd, Co and Zn and also encompasses the highest concentrations of Ag, As, Li and Ni. The concentrations of these elements are also higher than those reported by Pinto et al (2019), for unpolluted sediments of Sepetiba Bay, namely for As, Cd, Co, Cu, Mn, Cu, Ni, Pb, Sr and Zn. The comparison of the distribution maps of the concentration of the trace elements with the granulometric map of Sepetiba Bay developed by Pereira (1998) points out that there is some relationship between metal concentrations versus grain size. Most of the metals were adsorbed on grains of smaller size such as clay, silt and very fine sand.…”
Section: Distribution Of Trace Elemental Concentrationscontrasting
confidence: 57%
“…On the other hand, similarly to the previous region, the northern area presents the highest levels of Cd, Co and Zn and also encompasses the highest concentrations of Ag, As, Li and Ni. The concentrations of these elements are also higher than those reported by Pinto et al (2019), for unpolluted sediments of Sepetiba Bay, namely for As, Cd, Co, Cu, Mn, Cu, Ni, Pb, Sr and Zn. The comparison of the distribution maps of the concentration of the trace elements with the granulometric map of Sepetiba Bay developed by Pereira (1998) points out that there is some relationship between metal concentrations versus grain size. Most of the metals were adsorbed on grains of smaller size such as clay, silt and very fine sand.…”
Section: Distribution Of Trace Elemental Concentrationscontrasting
confidence: 57%
“…Where Cx is the concentration of the x element whose enrichment is to be determined and Cn is the concentration of the n normalizing element assumed to be characteristic of the baseline. For the baseline, the values estimated by Pinto et al (2019) were considered. In the present study, the Al was considered as normalizer.…”
Section: Concentrations Ofmentioning
confidence: 99%
“…Since Al, is a widely used element as a geochemical normalizer to minimize possible effects of sediment granulometric and mineralogical heterogeneity (Machado et al, 2008), representing the clay minerals sedimentary component, as suggested by Soares de Almeida et al 2019. The variation of PTE contents was compared with the baseline value, by dividing the concentration of each element (Cmetal) in the sediments by the respective the baseline (Cbaseline) in the study area estimated by Pinto et al (2019). Tomlinson et al (1980) named this ratio as contamination factor (CF).…”
Section: Concentrations Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the sedimentary evolution of Sepetiba Bay indicate that the present area was already exposed to subaerial processes during the last marine regression, in the Upper Pleistocene (between ≈127-20 ka; Monroe and Wicander, 2005). Subsequently, the last transgression, in the Late Pleistocene-Holocene drowned this area (Roncarati and Barrocas, 1978;Suguio, 2003;Pinto et al, 2016Pinto et al, , 2019Cunha et al, 2009Cunha et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%